Association of T352C and A16974C polymorphisms with lepromatose leprosy in Cuban patients - Estela Morales Peralta; Yadira Hernández Pérez; Kilenda Peñalver Morales; Yulié Lamas Torres; Raisa Rumbaut Castillo; Teresa Collazo Mesa (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Leprosy is an infectious disease caused by Mycobacterium leprae. Dermatoglyphic patterns of Cuban patients with lepromatose leprosy showed evidential signs of the existence of genetic predisposition to the development of this disease, which suggests a search for the association with molecular polymorphisms of higher degree of accuracy. Among them, some of the most studied are the T352C vitamin D receptor gene and the A16974Cof the IL12p40 gene, which relative usefulness depends on the population.  Objective:To determine whether there is an association between the T352Cand A16974C polymorphisms with lepromatose leprosy in Cuban patients. Material and methods:An observational analytical case-control type genetic association study was conducted where patients with lepromatose leprosy and controls were studied. Genotypes related to T352Cand A16974C polymorphisms were identified in each group.  Pearson´s chi square test was used to determine whether the controls were in Hardy-Weinberg equilibrium, and also whether there was a relation between polymorphisms and the presence of diseases. Results: There were 32 patients under study for T352C polymorphism, and 42 for A16974C. The controls were 64 and 44, respectively; and these were in Hardy-Weinberg equilibrium.  No association between T352Cand A16974C polymorphisms with lepromatose leprosy was detected.  Conclusions:  T352Cand A16974C polymorphisms are not useful as a predisposing risk factor in the group of Cuban patients with lepromatose leprosy studied. Keywords: Leprosy, genetic polymorphism, genetic predisposition to disease, Cuba, Hardy-Weinberg equilibrium, alleles.